PROFESSIONAL ADAPTATION OF YOUNG SPECIALISTS: DEFINITION AND LEGAL ASPECT OF IMPLEMENTATION - Kolesnikova V.V. (Pressing Problems of Public Administration, 2018)
The paper highlights approaches to the concept of ’professional adaptation of young specialists’,analyzes the legal aspects of young people’s adaptational capacities, and proves that the systemof professional adaptation of staff is used to improve the working process quality. It is stated thatprofessional adaptation of a person allows determining the appropriateness of a person’s choice ofprofession, creates conditions for adaptation of a young person to professional requirements, rapidacquision of knowledge, skills and abilities, improvement of the level of professional excellence.